Cigarro eletrônico na geração z: análise cienciométrica global (2014-2024) e estratégias pedagógicas de enfrentamento - Melger, Eloisa Checo (Universidade Federal de São Carlos, 2025)
This study conducted a scientometric and qualitative analysis of international scientific production on the use of electronic cigarettes among adolescents, from 2014 to 2024, with an emphasis on the pedagogical and sociocultural implications of these findings. The results reveal an expanding field, but one marked by strong geographic concentration, predominantly in highincome countries, especially the United States, and by an epistemological predominance of the areas of Medicine and Public Health. This biomedical centrality directs the discussion towards notions of risk, dependence, and behavioral surveillance, relegating educational and critical perspectives to the background. The co-authorship networks highlight the presence of articulated scientific centers, led by authors such as Harrell, Loukas, Clendenen, Kelder, Perry,and Pasch, dedicated primarily to the study of risk factors, the effects of marketing, and school prevention policies. The reviewed physiological and neurobiological evidence indicates that exposure to e-cigarette aerosol compromises neural plasticity and hippocampal function, elucidating the greater vulnerability of the adolescent brain due to the late maturation of the prefrontal cortex and the responsiveness of the reward system. However, the study demonstrates that social determinants, such as socioeconomic status and inequality in exposure to marketing, are crucial factors in the initiation and maintenance of consumption, widening structural disparities. In this sense, the work argues that preventive interventions, when applied as universal models disconnected from the material and affective realities of students, reinforce pedagogical coloniality. Considering Paulo Freire and Michael Apple's Critical Pedagogy, this document proposes a differentiated teaching model that recognizes the social context of young people and prioritizes critical health literacy. The methodological proposal is structured around five pillars: the creation of dialogical spaces; critical media literacy; the accessible incorporation of neuroscience knowledge; cultural and artistic interventions; and a socioecological and community-based approach, aiming to strengthen critical autonomy and emancipatory citizenship.
Electronic cigarettes in generation z: a global scientometric analysis (2014–2024) and pedagogical strategies for prevention
Keywords: Vaping; Educação; Ensino; Bibliometria; Adolescentes; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade